Regulatory mandates and responses to uncomfortable knowledge: The case of country-by-country reporting in the extractive sector - Baudot, Lisa; Cooper, David J. (Accounting, Organizations and Society, 2022)
We examine responses to pressures to act on extractive firm country-by-country reporting (CbCR) by three regulators: the International Accounting Standards Board, the European Commission, and the Securities and Exchange Commission. Debates over CbCR of payments that extractive firms make to governments center on improvements to transparency, governance, and accountability and raise questions about the division of regulatory labor in terms of where and by whom global reporting issues are undertaken and why. Our comparative analysis suggests that while the three regulators resist or respond reluctantly to similar pressures to act on CbCR, each responds in distinct ways that reflect and impact regulatory mandates. Specifically, we show how the regulators’ responses constitute the purpose, problematize the objectives, and construct the perceived interests served by CbCR in relation to each regulator’s mandate. We highlight how these responses can be understood through modes of discursive ignorance (McGoey, 2019) and the uncomfortable knowledge (Rayner, 2012) that each regulator may engage with when pressures challenge how regulators make sense of the world. Our study highlights that regulatory responses are based partly on what regulators assume are their mandates, their legitimacy and ways of operating. It analyzes their self-understandings and defense mechanisms, thereby providing an elaboration of responses to pressures for action and offering a richer political economy of regulation that highlights sensemaking in these processes. We further elaborate on what these responses imply for the division of regulatory labor around pressures to act on global reporting issues, as well as broader implications for participation in and ignorance around accounting regulatory projects.